1996
DOI: 10.1002/(sici)1099-1573(199605)10:3<251::aid-ptr808>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Extracts of Herbal Plants used in the Traditional Medicine of Bahrain

Abstract: Petroleum ether, methanol, hexane, butanol and aqueous crude extracts of the whole aerial parts of Suaeda vermiculata, Prosopis farcta, Capparis spinosa and Salsola villosa exhibited variable degrees of antimicrobial activity. Extracts had low to moderate actvity against four bacterial and two fungal species compared with that exerted by antibiotics. The petroleum ether extract of S. vermiculata and the butanol extract of S. villosa had high antifungal activity against Candida albicans and Fusarium oxysporum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…The mentioned researchers claimed that sensitivity of microorganism to chemoterapeutic compounds can change even against different strains. In similar studies (Chiang et al 1992;Mahansen 1996;Kıvçak et al 2002;Uzun et al 2002;Ateş et al 2003;Soares et al 2003;Dülger 2005;Kırbag et al 2005;Nair 2005;Şengül et al 2005;Vieria et al 2005;Kumar et al 2006;Mathabe et al 2006;Magalhes et al 2006), the extract of various plants inhibited the growth of some microorganisms at different ration. Different plants possess different constituents in different concentration, which account for differential antimicrobial effect, as also suggested.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The mentioned researchers claimed that sensitivity of microorganism to chemoterapeutic compounds can change even against different strains. In similar studies (Chiang et al 1992;Mahansen 1996;Kıvçak et al 2002;Uzun et al 2002;Ateş et al 2003;Soares et al 2003;Dülger 2005;Kırbag et al 2005;Nair 2005;Şengül et al 2005;Vieria et al 2005;Kumar et al 2006;Mathabe et al 2006;Magalhes et al 2006), the extract of various plants inhibited the growth of some microorganisms at different ration. Different plants possess different constituents in different concentration, which account for differential antimicrobial effect, as also suggested.…”
Section: Resultsmentioning
confidence: 85%
“…The effect of plant extracts on microorganism have been studied by a very large number of researchers in different parts of the world (Mahansen 1996;Kıvçak et al 2002;Uzun et al 2002;Ateş et al 2003;Dülger 2005;Kırbag et al 2005;Nair 2005;Şengül et al 2005;Kumar et al 2006;Mathabe et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of one study (Mahasneh et al, 1996), no previous reports on the antifungal properties and chemical nature of the inhibitory compounds of the examined plant taxa could be found in the literature. In their study, Mahasneh et al (1996) reported a mild inhibitory effect (average 11.5 mm) of various extracts of Capparis spinosa against Fusarium oxysporum and Candida albicans.…”
Section: Discussionmentioning
confidence: 96%
“…The practice is still strong in the treatment of minor ailments with these plants including ulcers, pneumonia, stomach disorders, rheumatism, diabetes, renal problems, and bronchitis (Abbas et al, 1992). Researchers are increasingly turning their attention to folk medicine and antimicrobial compounds from plant species used in herbal medicine in Bahrain (Abbas et al, 1992;Al-Saleh et al, 1993, 1997Mahasneh et al, 1996;Taha & Hashem, 2000). Moreover, herbal medicine is improved as an alternative effective solution to health problems and cost of pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation